THE EFFECT OF CHERRY (MUNTINGIA CALABURA) JUICE ON INCREASED MEMORY IN MICE (MUS MUSCULUS) BY MORRIS WATER MAZE METHOD - Maulita Saraswati; Krisantus Y Oeleu; Dhanisa Dwi N (Joseph: Journal of Science and Pharmacy, 2021)
Background: Cherry fruit (Muntingia calabura) contain are alkaloids, saponins, tannins, and flavonoids which serve to neutralize free radicals. Purpose: The research was conducted to know the effect of cherry fruit juice to increased memory in mice using Morris Water Maze (MWM) with the parameter time latency (the time it takes to reach the murine platform). Method: Cherry fruit (Muntingia calabura) was made in the form of juice, where cherry used as many as 50 g and then added 200 ml aquadest. A dose of cherry fruit respectively 0, 064 g/kg BW; 0.13 g/kg BW; 0.26 g/kgBW. Animal test used in this study was a White House mouse (Mus Musculus) male Balb/c strains which are divided in 5 groups, each group consists of 5 mice. There are 2 negative control group (aquadest), positive (Gingko biloba) and 3 treatment groups with cherry fruit juice (0.064; 0.13 0.26 g/kgBW). Mice induced by ethanol 10% orally. Each group of direnangkan treatment on Morris water maze to find the platform. Result: Data analysis was carried out by using one way ANOVA. The results showed that a third of the dose of cherry fruit juice 0.064; 0.13; 0.26 mg/kgBB mice can improve memory in mice. Conclusion: The effective dose of cherry fruit juice is 0.26 mg/dose kgBW because the equivalent positive control group.